'Way Out - Of This World!' Delia Derbyshire, Doctor Who and the British Public's Awareness of Electronic Music in the 1960s. Issue 1 (1st April 2014) - Butler, David
Abstract The composer and musician Delia Derbyshire (1937-2001) remains most famous for her arrangement and realisation of Ron Grainer's title theme for Doctor Who. Yet although providing the theme tune with its distinctive sounds, which would be featured in the programme's titles from 1963 until 1980, Derbyshire provided little else in terms of music for the Doctor's adventures during her time at the BBC Radiophonic Workshop. This article considers the impact of the Doctor Who theme tune on Derbyshire's career and the interest in electronic music that it generated amongst the British public in the 1960s.